Volleyball and COVID-19 emergency: experience of a high-level Italian club team - Piatti, M.; Turati, M.; Bigoni, M.; Gaddi, D. (Sport Sciences for Health, 2021)
At the beginning of 2020, the world was distraught with a new invisible enemy: COVID-19 disease is the effect of SARS-CoV-2 infection, a new virus that suddenly changed our life. From the first cases reported to the World Health Organization (WHO) by Chinese national health authorities in the Wuhan city in the last days of 2019, this insidious disease has grown, causing a pandemic that paralyzed different human activities. Italy and especially the Lombardy region were seriously hit by COVID-19, causing high pressure on hospitals and intensive care; nurses and doctors from every specialization (surgeons, radiologists, orthopedics, dermatologists, etc.) in the main hospitals were rapidly converted to the front line against a new disease with unknown mid-long-term effect and consequences. Simultaneously, the Italian government—as the first one in Europe—took drastic measures limiting the daily life of everyone. Following the principles of "extra caution" and "stay at home", a lot of aspects of our lives changed; among other things, amateur and high-level sports were interrupted. Volleyball is a very popular sport in Italy, and it is played by around 200 million people worldwide; its stop changed the life of athletes and many other people directly or indirectly involved in the Italian volleyball movement. What happened during this period effected everyone deeply. Consequences from social-psychological-economical points of view will affect volleyball for a long time. Volleyball is considered a no contact sport, but contacts happen for greetings, exultations and accidentally during the game. SARS-CoV-2 typical transmission is through respiratory droplets passing from person to person. During the matches, the ball passes all the time from one player to another and could thus be considered a potential vehicle for the virus; on the other side, there is no evidence that the virus can be spread through sweat. Superlega, the male Italian volleyball first league, attracts a lot of people and fans. Main games could aggregate a large number of spectators; during the season 2018-19, a match brought together more than 12,000 spectators in the arena. Considering all these elements, the continuation of normal sport activities became incompatible with the COVID-19 pandemic. Nowadays, after a complex organization needed to restart there is a great uncertainty about prosecution of the new season. Such a complicated situation was characterized by the uncertainty of the measures taken by the governments of the various countries without homogeneous decision-making and rules. It is clear that this global crisis has caused and will create major organizational, financial and social disruption to athletes, coaches, clubs and sports federations.